2012
DOI: 10.3393/jksc.2012.28.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Anastomosis by Use of a Memory-shaped Compression Anastomosis Clip (Hand CAC 30): Early Clinical Experience

Abstract: PurposeThe safety and the efficacy of the compression anastomosis clip (Hand CAC 30) have been demonstrated by animal studies. This study was designed to evaluate the clinical validity of the Hand CAC 30 in enterocolic side-to-side anastomosis after colonic or enteric resections.MethodsA non-randomized prospective data collection was performed for patients undergoing a side-to-side anastomosis using the Hand CAC 30. Eligibility criteria for the use of the Hand CAC 30 were for anastomoses between the colon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…However, the HS ileocolostomies resulted in more granulation tissue on both postoperative days 5 and 7. Previous studies of CAC anastomoses in humans have indicated that they are as safe and effective as stapled anastomoses [2,[5][6][7][8][9][10][11][12][13]. The safety of this device has also been documented in animal studies [28,29], including a comparison between CAC and stapled jejunojejunal anastomoses in pigs, in which a histological examination of the CAC anastomoses demonstrated a complete mucosal lining with no evidence of stricture formation at two months [29].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the HS ileocolostomies resulted in more granulation tissue on both postoperative days 5 and 7. Previous studies of CAC anastomoses in humans have indicated that they are as safe and effective as stapled anastomoses [2,[5][6][7][8][9][10][11][12][13]. The safety of this device has also been documented in animal studies [28,29], including a comparison between CAC and stapled jejunojejunal anastomoses in pigs, in which a histological examination of the CAC anastomoses demonstrated a complete mucosal lining with no evidence of stricture formation at two months [29].…”
Section: Discussionmentioning
confidence: 88%
“…The use of CACs in humans has been reported [2,5,6,[7][8][9][10][11][12][13], including a comparison of CAC anastomoses with stapled anastomoses in the stomach, small intestine, and colon [5][6][7][8]13]. However, to the best of the current authors' knowledge, no comparison of healing between CAC and hand-sewn (HS) anastomoses has previously been reported.…”
mentioning
confidence: 77%
“…Se presentaron 2 complicaciones mayores (14%), que consistieron en una dehiscencia de pared y en una de anastomosis, y una complicación menor (7%), que corresponde a infección de tejidos blandos. El sangrado transoperatorio fue de 98 ml (20-300); el inicio de la vía oral fue en promedio al segundo día del postoperatorio, y la estancia hospitalaria fue de 4 días en promedio (2)(3)(4)(5)(6)(7)(8)(9)(10). Un paciente con anastomosis del íleo-recto presentó dehiscencia al cuarto día del postoperatorio y requirió reintervención, realizándose una nueva anastomosis con dispositivo de grapeo protegida con ileostomía en asa.…”
Section: Resultsunclassified
“…6 The conventional hand suturing and stapling techniques are currently the most popular methods for restoration of intestine continuity. 2 The 3 main complications of intestinal anastomosis are leakage, bleeding, and stenosis. Leakage is the most common postoperative complication, which may lead to mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The process of intestinal anastomosis is a major technical component of gastrointestinal surgery, and the hand-suturing method, which is widely used, is the initial procedure for intestinal anastomosis. 1 Other methods have been developed for anastomosis including linear and circular stapling, 2 compression rings, 3,4 tissue glue, 5 and laser anastomosis. 6 The conventional hand suturing and stapling techniques are currently the most popular methods for restoration of intestine continuity.…”
Section: Introductionmentioning
confidence: 99%